Comorbidities in a Cohort of 66 Patients With Psoriatic Arthritis Mutilans—Results From the Nordic PAM Study - Mistegård, Josephine; Gudbjornsson, Bjorn; Lindqvist, Ulla; Laasonen, Leena; Ejstrup, Leif; Ståhle, Mona; Iversen, Lars (Frontiers in Medicine, 2021)
Objective: Psoriatic arthritis mutilans (PAM) is the most severe phenotype of psoriatic arthritis due to excessive bone erosion causing joint destruction and decreased functional capacity. The aim of this study was to investigate the prevalence of comorbidities among patients with PAM and the association between comorbidities and joint involvement. Methods: A total of 66 patients aged ≥ 18 years from the Nordic countries with past or present psoriasis along with at least one mutilated joint were included in the present study. Results: The median number of comorbid conditions per patient was 1 (interquartile range (IQR) 0-2) and 16.7% reported three or more comorbidities. The most frequent comorbidity was hypertension (36.4%). The median number of mutilated joints per patient was 3 (IQR 1-8.3; range 1-38). Conclusion: Two thirds of the patients with PAM reported comorbid conditions and the most frequent was hypertension which affected more than a third of the patients. However, this study was unable to detect any association between comorbidities and the severity of PAM.